Testing the Validity of Arbitrage Pricing Theory: A Study on Dhaka Stock Exchange Bangladesh - Rahman, Syed Mohammad Khaled; Mazumder, Priyanka (Financial Risk and Management Reviews, 2021)
The purpose of the study was to test the validity of Arbitrage Pricing Theory (APT) in Dhaka Stock Exchange (DSE) of Bangladesh. Secondary data has been used which was composed of observable macroeconomic and stock market variables. Study period was from January 2013 to October 2018, making a total of 70 monthly observations. Study found that interest rate and exchange rate has significant influence but market capitalization and tax rate have insignificant impact on return of DS-30 index. Except exchange rate, other three variables were negatively related with DS-30 index return. 1% increases in exchange rate results 0. 993% increase in stock prices while 1% increases in interest rate results 0. 486% decrease in stock prices and vice-versa. Strong negative correlation was seen between interest rate and stock index return. APT have failed to fully explain the change of DS-30 index return due to presence of two insignificant explanatory variables. This research has practical implications on stock market participants as investors’ optimal strategy largely influenced by precision of asset pricing models. This research has also policy implications for Securities & Exchange Commission, government, and other regulators as findings of the study will assist them to develop more efficient capital market.